La cérémonie du thé dans la peinture anglaise du dix-huitième siècle - Sophie Loussouarn (Revue Française de Civilisation Britannique)
A new genre appeared in eighteenth-century Britain with the development of the tea trade and changing lifestyles. The tea party was widespread among the ruling classes and the traders of the East India Company who were painted in conversation pieces. These paintings, which brought together families and sometimes friends, focus on the social status of the characters shown in their environment and highlight the changes in family life. This national genre evolved with sensibilities and was even ridiculed by some caricatures at the end of the century.